ESTETIKA HUMANISTIK PUISI-PUISI PENYAIR ASAL MADURA - Helmi, M. (Program Studi Pendidikan Bahasa Indonesia STKIP-PGRI Bangkalan, 2018)
Madurese poets in quality and quantity have been recognized as one of the sources of wealth of Indonesian literary treasures. This is evidenced by some evidence of the achievements of Madurese poets who received many awards. Like Abdul Hadi WM, D Zawawi Imron, Jamal D Rahman. The poetry in the interests of this research was then used as a data source. Research on the works of their poets through the Humanistic Aesthetic concept Hans Georg Gadamer gave birth to findings that in poetry Madurese poets were found bildung, census communis, practical considerations, and different tastes. Aside from being a form of learning, another reason that encourages researchers to conduct a study of the poems of Madurese poets, namely the attempt to traditionalize the culture of poets who come from Madura. Especially the problem of poetry that leads to the character of each poet.